2016
DOI: 10.1038/srep32756
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin Attenuates Airway Mucus Overproduction via Inhibition of the GABAergic System

Abstract: Airway mucus overproduction is one of the most common symptoms of asthma that causes severe clinical outcomes in patients. Despite the effectiveness of general asthma therapies, specific treatments that prevent mucus overproduction in asthma patients remain lacking. Recent studies have found that activation of GABAA receptors (GABAAR) is important for promoting mucus oversecretion in lung airway epithelia. Here, we report that luteolin, a natural flavonoid compound, suppresses mucus overproduction by functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 53 publications
0
28
0
Order By: Relevance
“…In this study, both in vivo and in vitro experiments indicated that amygdalin may help decrease the expression of TGF‐β1 and the phosphorylation of smad2/3, inhibiting the EMT process by the TGF‐β/smad pathway to some extent. We hypothesize that amygdalin may competitively combine with the TGF‐β receptor, affecting the expression of TGF‐β and the phosphorylation levels of smad2 and smad3 (Shen et al, ). In addition, we also found that after intervention with amygdalin, the inflammatory response and lung injury in COPD mice were reduced significantly, indicating a certain anti‐inflammatory effect of amygdalin, but this mechanism needs further study.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, both in vivo and in vitro experiments indicated that amygdalin may help decrease the expression of TGF‐β1 and the phosphorylation of smad2/3, inhibiting the EMT process by the TGF‐β/smad pathway to some extent. We hypothesize that amygdalin may competitively combine with the TGF‐β receptor, affecting the expression of TGF‐β and the phosphorylation levels of smad2 and smad3 (Shen et al, ). In addition, we also found that after intervention with amygdalin, the inflammatory response and lung injury in COPD mice were reduced significantly, indicating a certain anti‐inflammatory effect of amygdalin, but this mechanism needs further study.…”
Section: Discussionmentioning
confidence: 99%
“…The active component of Perilla frutescens, luteolin, is believed to have anti-allergic, anti-inflammatory, and anti-oxidative effect (Seelinger et al, 2008;Lee et al, 2010Lee et al, , 2015Shen et al, 2016;Jang et al, 2017;Kamei et al, 2017;Kim and Yun, 2017;Nunes et al, 2017). Several possible mechanisms of the anti-allergic effects of luteolin have been proposed by previous studies and these include inhibition of pro-inflammatory cytokines, reduction of IgE production, and reduction of mucin production (Kritas et al, 2013;Lee et al, 2015;Shen et al, 2016;Jang et al, 2017). In the present study, we investigated the effects and mechanism of luteolin in a murine AR model.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, luteolin reduced cellular infiltration in pulmonary parenchyma and nasal tissue, as well as inflammatory cells in bronchoalveolar lavage fluid in a murine model of allergic asthma and rhinitis (Jang et al, 2017). Shen et al (2016) found that luteolin could attenuate airway mucus overproduction in allergic mice.…”
Section: Introductionmentioning
confidence: 96%
“…In lipopolysaccharide-induced pneumonia, luteolin reduces apoptosis and inhibits expression of inflammatory cytokines [31]. It also reduces the excessive secretion of mucus in the lung airway epithelium [32]. In addition, luteolin has antiviral properties, which interferes with viral replication in the early stages of influenza A virus infection by inhibiting the expression of its coat protein I complex, thus blocking virus invasion and endocytosis [33].…”
Section: Discussionmentioning
confidence: 99%